2012
DOI: 10.1016/j.apergo.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wearing an unstable shoe on thigh and leg muscle activity and venous response in upright standing

Abstract: Purpose: To quantify the effect of unstable shoe wearing on muscle activity and haemodynamic response during standing.Methods: Thirty volunteers were divided into 2 groups: the experimental group wore an unstable shoe for 8 weeks, while the control group used a conventional shoe for the same period. Muscle activity of the medial gastrocnemius, tibialis anterior, rectus femoris and biceps femoris and venous circulation were assessed in quiet standing with the unstable shoe and barefoot.Results: In the first mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 51 publications
2
30
1
1
Order By: Relevance
“…The transfer of changes associated to WUS to the barefoot condition has not been found in measurements in other functional activities like standing [36] and walking [37]. Our findings suggest that there is a long-term transfer of changes associated with the unstable shoe condition to barefoot condition, in a higher postural control demand task.…”
Section: Influence On Muscle Activity At the Individual Muscle Levelcontrasting
confidence: 48%
See 1 more Smart Citation
“…The transfer of changes associated to WUS to the barefoot condition has not been found in measurements in other functional activities like standing [36] and walking [37]. Our findings suggest that there is a long-term transfer of changes associated with the unstable shoe condition to barefoot condition, in a higher postural control demand task.…”
Section: Influence On Muscle Activity At the Individual Muscle Levelcontrasting
confidence: 48%
“…Previous research reported that these shoes improved reactive balance in children with development disabilities [6], improved static and dynamic balance in adults with osteoarthritis [7] and in middle-aged adults [8,9], and also in young subjects in dynamic conditions like standing on a moveable platform [10]. Electromyography studies revealed changes in the ankle joint during quiet standing [8,11], gait and running [12,13]. These are important findings since standing sway is highly correlated with ankle joint rotation, as muscles crossing this joint are able to provide the sensory information required to maintain upright standing [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…The results of the present study encourage the use of unstable shoes as a beneficial ergonomic intervention, since they demonstrate that the instability provided by wearing the shoes leads to a reorganisation of postural control that result in increased performance and effectiveness during upright standing. This reorganisation of upright standing postural control is accompanied by increased calf muscle activity, improving venous return (Sousa, et al, 2012). However, studies on the influence of wearing unstable shoes on subjective rating of fatigue and discomfort while standing are demanded to support our hypothesis.…”
Section: Wearing Unstable Shoes Can Be a Beneficial Ergonomic Intervementioning
confidence: 61%
“…However, divergence exists as to the benefits from wearing this kind of shoes on postural control. Previous research has demonstrated that wearing this kind of unstable shoes regularly leads to changes in muscle activity level, mainly at the ankle joint, during upright standing (Sousa et al, 2012) and to decreased centre of pressure (CoP) excursion in young subjects (Landry et al, 2010); although no changes have been observed in the mean velocity of the CoP in mid-aged women (Ramstrand et al, 2010), neither in the CoP excursion in one-leg stance in young subjects (Turbanski et al, 2011). This divergence could result from the few parameters analysed, as a larger set of measures is required to detect differences in postural control (Pavol, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…According to recent studies, one of the significant characteristics of footwear, which might influence muscular activity pattern and haemodynamic response in lower extremities, is the rocker shape of sole design that produces instability during standing and walking (Nigg et al, 2012;Sousa et al, 2012). Several scientific studies have investigated the impact of unstable footwear (shoe with a rocker sole) on biomechanical objective measures during walking so far.…”
Section: Introductionmentioning
confidence: 99%